THE EFFECT OF GOOD CORPORATE GOVERNANCE ON EARNING MANAGEMENT WITH THE BONUS PLAN AS A MODERATING VARIABLES - Mayndarto, Eko Cahyo; Murwaningsari, Etty (International Journal of Social and Management Studies, 2021)
The purpose of this study was to determine the effect of Good Corporate Governance (GCG) on Earnings Management moderated by a Bonus Plan. Conflicts that occur due to separation of ownership are called agency conflicts that can cause agency problems between owners and managers. This tendency makes earnings management practices more frequent by management. Where earnings management is part of creative accounting which provides opportunities for managers to act opportunistically, namely obtaining personal benefits. In an effort to protect each stakeholder's interests, good and correct corporate governance is needed or commonly referred to as good corporate governance. Design / methodology / approach - This study uses secondary data in the form of financial reports on Islamic banking in Indonesia for the period 2012-2019 The analysis used in this study is a multiple regression analysis model using hypothesis testing. Findings - There is no influence of the Sharia Supervisory Board (DPS) on earnings management, there is a significant influence of independent commissioners on earnings management, there is a significant effect of the audit committee on earnings management, there is no significant effect of the sharia supervisory board with bonus plans on earnings management , There is no significant effect of the independent commissioner with bonus plan moderated on earnings management. There is a significant effect of the audit committee with bonus plan moderated on earnings management. Practical implications - The results will increase awareness of the importance of implementing Good Corporate Governance (GCG) in Islamic Banks in Indonesia to reduce earnings management practices. Originality / value - This study wants to find out whether the bonus plan can moderate Good Corporate Governance towards Earnings Management in Islamic Banking in Indonesia.